Simple anthropometric measures correlate with metabolic risk indicators as strongly as magnetic resonance imaging–measured adipose tissue depots in both HIV-infected and control subjects - Scherzer, Rebecca (2008)
BACKGROUND: Studies in persons without HIV infection have compared percentage body fat (%BF) and waist circumference as markers of risk for the complications of excess adiposity, but only limited study has been conducted in HIV-infected subjects. OBJECTIVE: We compared anthropometric and magnetic resonance imaging (MRI)–based adiposity measures as correlates of metabolic complications of adiposity in HIV-infected and control subjects. DESIGN: The study was a cross-sectional analysis of 666 HIV-positive and 242 control subjects in the Fat Redistribution and Metabolic Change in HIV Infection (FRAM) study assessing body mass index (BMI), waist (WC) and hip (HC) circumferences, waist-to-hip ratio (WHR), %BF, and MRI-measured regional adipose tissue. Study outcomes were 3 metabolic risk variables [homeostatic model assessment (HOMA), triglycerides, and HDL cholesterol]. Analyses were stratified by sex and HIV status and adjusted for demographic, lifestyle, and HIV-related factors. RESULTS: In HIV-infected and control subjects, univariate associations with HOMA, triglycerides, and HDL were strongest for WC, MRI-measured visceral adipose tissue, and WHR; in all cases, differences in correlation between the strongest measures for each outcome were small (r ≤ 0.07). Multivariate adjustment found no significant difference for optimally fitting models between the use of anthropometric and MRI measures, and the magnitudes of differences were small (adjusted R(2) ≤ 0.06). For HOMA and HDL, WC appeared to be the best anthropometric correlate of metabolic complications, whereas, for triglycerides, the best was WHR. CONCLUSION: Relations of simple anthropometric measures with HOMA, triglycerides, and HDL cholesterol are approximately as strong as MRI-measured whole-body adipose tissue depots in both HIV-infected and control subjects.